Discordant associations of educational attainment with ASD and ADHD implicate a polygenic form of pleiotropy - Ellen Verhoef (Nature Portfolio, 2021)
Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder are co-occurring neurodevelopmental conditions displaying strong, discordant polygenic associations with educational attainment. Here, the authors study genetic mechanisms underlying genome-wide correlation patterns across these traits.